Ethno-pedagogical Study of Siat Sarang: A Local Wisdom Approach to Conflict Prevention - Yasa, I Wayan Putra; Suastra, I Wayan; Arnyana, Ida Bagus Putu; Purnawati, Desak Made Oka; Arta, Ketut Sedana (SOSHUM : Jurnal Sosial dan Humaniora, 2023)
The aims of this research are to 1) reconstruct the background of the Siat Sarang tradition in the Selat Traditional Village, Karangasem, Bali, 2) explore ethno-pedagogical values ​​as character values ​​of the Siat Sarang tradition that can prevent conflict, and 3) Reconstruct a model of ethno-pedagogical practice in Siat Sarang tradition as a safety valve based on local wisdom for conflict prevention. Then, this phenomenon is studied using qualitative methods with a critical ethnographic model—data collection using in-depth interviews, observation, and literature study. Then, evaluate its validity by triangulating methods and sources. The data was then analyzed using critical ethnography, resulting in a comprehensive survey of strategies, values​​, and implementation models. The research results show that the Siat Sarang tradition has local wisdom values​​, which can be used as a safety valve to prevent societal conflict. The values ​​contained in it are religious, social, sportsmanship, and ethnic-based educational values ​​(ethno-pedagogy). These values ​​have been inculturated in families, communities, and schools. The results of this research mean that tradition has a role in preventing conflict. The form is local wisdom, which has ethno-pedagogical value in the form of character education.